Effects of Pre-Surgical Education and Physical Therapy Training for Dyspnea Prevention in Patients Undergoing Valvular Cardiac Surgery - Ibrar, Iqra; Shabbir, Sana; Ahmad, Haseeb; Zafar, Madiha; Hassan, Talha; Waheed, Mariam (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the Effects of Pre-operative education and physical therapy training for dyspnea prevention in patients undergoing valvular cardiac surgery. Methods: A Prospective RCT was performed on sample size of 40 patients of cardiac valvular disease that were obtain from Faisalabad Institute of cardiology. At the time of admission, all patients were tested by baseline dyspnea index then the subjects were randomly assigned into two groups by computerized random generator. Both groups were having education but treatment group were having additional breathing exercises and functional tasks for 10 minutes in 1st week regularly and 1 hour in 2nd week regularly. Each group were tested again by BDI after the treatment on second post-op day. Tracheal extubation and eye-opening time were also noted as outcome measures of study. Results were compiled on SPSS.20 for finding post-operative dyspnea. Results: Pre-operative and post-operative findings showed that the patients of treatment group performed better than control group as the effects of pre-operative treatment on dyspnea by total baseline dyspnea index is significant (p<0.05) as well as the treatment group had significant reduction in eye-opening and tracheal extubation time in comparison of control group having (p<0.05). Conclusion: The results shows that in patients of valvular cardiac surgery, pre-surgical education and physical therapy training showed significant reduction in post-surgical dyspnea, tracheal extubation and eye-opening time.